Causes of injuries in young female judokas - Witkowski, K.; Mslinski, J.; Stefaniak, T.; Weczorek, I. (Archives of Budo, 2012)
Background and Study Aim: The health aspect of physical activity is not often referred to "effort safety" and "motor safety" of those engaged in this type of activity. The benefits of systematic training to humans are stressed instead. Yet even people for whom sport is a leisure activity often put in extreme physical effort. The aim of the paper is to expand the knowledge of the causes and locations of injuries in young female judokas. Material and Methods: We studied 30 females (14 juniors and 16 seniors) who were leading Polish judokas of various weight categories with medals from Polish Judo Championships and were aged 17-26 (average age was 20.9 years). On average, they had been training for 11 years. The study was based on our own questionnaire with 60 semi-open and closed questions. The questions concerned the personal characteristics of each athlete, including age, gender, weight, training experience, sports class as well as detailed information concerning factors that were the causes of each injury, according to the respondents. Detailed questions also dealt with the type and location of injuries as well as various aspects of judo training. In our statistical analysis we used a proportional ratio (in %), while the calculation of some empirical data (considered as variables and hypothetically interacting with each other) were based on the ?2 test. Results: Most injuries in young female judokas occur during periods of the most intense training activity. These are usually heavy injuries that exclude the injured person from training for more than 4 weeks. Light injuries in judo occur less often than moderate injuries. Injuries in judo are caused by aggressive fighting which, however, does not determine their seriousness. Aggressive behaviour was observed in all groups of judokas with light, moderate and heavy injuries. Conclusions: An injury during a judo fight is a complex, multi-factor phenomenon. Coaches should carefully analyse training and competition fights of all judokas in order to individually influence the events that may lead to even light injuries.